A comparative and cross-sectional study on the prevalence of risk factors for mouth ulcer and oral cancers in migrants and native population of a tourist city of Rajasthan - Kumar, Rupesh; Hathi, Maitri R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Oral cancer is a major non communicable disease which is considered as one of the major public health problems in India. It can easily be prevented through early detection and stopping the associated risk factors like smokeless tobacco. The objective of the study was to assess the prevalence of risk factors for mouth ulcer and oral cancer among migrants of Udaipur city and comparing them to its native population. Methods: A cross sectional study was conducted to know the prevalence of smokeless tobacco and other associated risk factors and recommend the preventive strategies based on study findings which consisted of 384 migrants and 384 native population of Udaipur, Rajasthan during May 2016 to April 2017. Results: Majority of migrants 36.46% and native 34.11% were in age group of 28-37 years. Out of 384, 89 (23.18%) and 117 (30.47%) migrants and native were having habit of smokeless tobacco chewing respectively (statistically significant p<0.05). The prevalence of smoking among migrants and native were 34.38% and 24.48% respectively (statistically significant p<0.05). A major risk factor of mouth ulcer was same smokeless tobacco chewing in both migrants (57.14%) and in native (66.66%). Migrants with the habit of smokeless chewing were unable to open mouth was recorded (69.04%) whereas native population was recorded (36.66%) (statistically significant p<0.05).. Conclusions: Smokeless tobacco chewing habit in both migrants and native population is a significant risk factor for mouth ulcer and oral cancer.